Learning trajectory on understanding monetary values for autistic students through a modified monopoly game - Marhamah; Putri, Ratu Ilma Indra; Zulkardi; Hartono, Yusuf (Universitas Hamzanwadi, 2025)
Children with autism spectrum disorder (ASD) often have difficulty understanding abstract concepts, such as monetary values, due to limitations in executive functioning and concept generalization. This study aimed to develop and test a learning trajectory for understanding monetary values through a modified Monopoly game according to the characteristics of autistic students. The study employed a design research approach with validation type, using hypothetical and actual learning trajectory (HLT-ALT) analysis through the stages of preparation, design experiments (pilot and teaching experiments), and retrospective analysis of the data. The research subjects were eight autistic students at the junior high school level at SLB Bina Autis Mandiri, Indonesia. Data were collected through student activity sheets, observations, interviews, and documentation and then analyzed qualitatively. The results showed that the learning trajectory consisting of four activities (playing modified Monopoly, recognizing the value of money, counting the number of pictorial patches of money, and adding up the value of money) effectively helped students gradually understand the concept of monetary value. Game-based activities also increased students' engagement and understanding of the material. This study contributes to a replicable and inclusive learning trajectory that integrates structured gameplay with mathematical reasoning for students with autism.